Bridging the Gap Between Theory and Practice: Enhancing Small Businesses through Student-Led Community Engagement - Ayansola Olatunji Ayandibu (Indonesian Journal of Community Engagement, 2025)
This article presents the outcomes of an action research project conducted by 30 Honours students from a comprehensive university in KwaZulu-Natal, South Africa. The academic assignment required students to engage directly with 30 small and informal businesses operating in rural and peri-urban communities. The main objective was to identify operational challenges faced by these businesses and propose context-specific, practical solutions. The study highlights the value of experiential learning in simultaneously enhancing student competencies and contributing to local community development. Using business diagnostic tools such as SWOT and PESTEL analyses, students assessed each business and co-developed tailored interventions, ranging from infrastructure improvements to digital marketing strategies. Commonly identified problems included power outages, poor financial literacy, informal operations, low customer retention, and limited scalability. Corresponding solutions included the use of solar energy, social media marketing, basic bookkeeping templates, and partnership development strategies. Reflections submitted by students demonstrated high levels of contextual awareness, creativity, and diagnostic accuracy, though challenges were observed in areas such as research triangulation, feasibility planning, and academic writing. The project culminated in the development of a Mini Solution Toolkit, featuring templates and checklists tailored to the needs of informal entrepreneurs. This research contributes to the growing body of literature on community-engaged scholarship and practical entrepreneurship education, with implications for curriculum design, local policymaking, and small enterprise support. It positions academic institutions as potential catalysts for inclusive economic development.